Prévention des TMS dans la durée : des acteurs institutionnels facilitent une démarche d’entreprise - Elisabeth Tayar; Christophe David; Marc Viel (Perspectives Interdisciplinaires sur le Travail et la Santé)
A departmental musculoskeletal disorder (MSD) prevention project was begun in 2003 on the initiative of the Anjou inter-company medical service and the Regional action for the improvement of working conditions in the Pays de Loire to respond to companies’ difficulties in establishing effective and ongoing projects. It brought together 6 volunteer companies in a commitment to a 5-year agreement.The institutional prevention actors provide, in a multi-disciplinary approach, a project methodology and the opportunity for exchanges and feedback between the companies. This accompanying action focused on the creation of working groups led by private consultants to consider situations that could lead to musculoskeletal disorders and to share decisions for change.After the project had been conducted in a bovine slaughterhouse for 3 years, an adaptation process is now being carried out. The evaluations are revealing human, organizational and technical changes. This experiment questions the role of institutional actors and the interest of the link between external actors and actors inside the company.